EVALUATION OF IDIOPATHIC SCOLIOSIS IN SUBTYPES OF PECTUS EXCAVATUM AND CARINATUM - Davi de Podesta Haje; Guilherme Antunes Barriviera; Marcos Vinícius Santana Silva; Caroline Kaori Maebayashi (Acta Ortopédica Brasileira)
ABSTRACT Objective: Evaluation of epidemiological data on Idiopathic Scoliosis in patients with different pectus subtypes. Methods: A medical record analysis of 418 patients with pectus, associated with idiopathic scoliosis above 10°, with research on: subtypes of pectus (Lateral Pectus Carinatum, Inferior Pectus Carinatum, Superior Pectus Carinatum, Broad Pectus Excavatum, and Localized Pectus Excavatum), and characteristics of the scoliotic curve (Cobb angle, laterality, and location). Results: The mean age was 14.6 years (22° mean Cobb, 52% females and 48% males). The most frequent kind of pectus was Inferior Pectus Carinatum (28%). The left-convex thoracolumbar type was the most frequent. Scoliosis was more severe in thoracic location and females. The main type was LPC (p < 0.05) in those with severe scoliosis. BPE was more present in men (68%), and LPC and SPC in women (p < 0.05). No significant differences were found between the pectus type and the side or location of the scoliosis curve. Conclusion: Depending on the subtype of pectus, the scoliotic curve presents distinct epidemiology and characteristics. Level of Evidence IV, Case Series – study prognostic.